Bioremediation of hydrocarbon containing wastewater in anoxic-aerobic sequential reactors. Issue 22 (1st October 2020) - Mallick, Subrat Kumar; Chakraborty, Saswati
ABSTRACT: Anoxic-aerobic sequential moving-bed reactors were operated for the degradation of synthetic petroleum refinery wastewater containing phenol (750 mg/L), hydrocarbons (1250 mg/L), S 2− (750 mg/L), NH4 + –N (350 mg/L), NO3 – N (1000 mg/L) and surfactant as nonylphenol-monoethoxylate (0.2 mmol/L). Kerosene, heavy oil and their mixture were used as hydrocarbon source. Anoxic reactor was a disc-bed reactor and aerobic reactor was moving-bed reactor operated at hydraulic retention times (HRT) of 48 and 16 h respectively at 27 ± 3°C. In anoxic reactor, removals of S 2− and NO3 – N were more than 99% along with 50–60% removal of hydrocarbons and phenol. Removal of organics deteriorated in anoxic reactor with heavy oil in feed having higher density and viscosity. Residual organics and NH4 + –N were removed in aerobic reactor with more than 99% efficiency. Biomass activity decreased in anoxic reactor and increased in aerobic reactor with an increase in density and viscosity of hydrocarbon in feed. Abiotic study confirmed most of the removals were due to biodegradation. GRAPHICAL ABSTRACT: UF0001